2020
DOI: 10.1007/s10551-020-04625-y
|View full text |Cite
|
Sign up to set email alerts
|

Progressive and Rational CSR as Catalysts of New Product Introductions

Abstract: Whereas extant literature has examined the overall effect of corporate social responsibility (CSR) on innovation, it is argued that CSR is a multidimensional concept encompassing both progressive activities concerning a firm's engagement in the social domain, as well as rational aspects pertaining to corporate governance practices and the protection of shareholder rights. This study integrates organizational hypocrisy with the knowledge-based view literatures to examine how different forms of CSR engagement af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 145 publications
(170 reference statements)
0
7
0
Order By: Relevance
“…By actively interacting and communicating with various stakeholders to improve or enhance the relationship between the firm and its stakeholders (Miller et al, 2018), involvement in ESG makes the firm more sensitive to the needs of its stakeholders (Porter & Kramer, 2011). In turn, companies can gain a more comprehensive and deeper understanding of the needs of their stakeholders (e.g., consumers) and thus seek more market opportunities to develop new products or services (Murcia, 2021).…”
Section: Differentiation Strategies and Firms' Esg Involvementmentioning
confidence: 99%
“…By actively interacting and communicating with various stakeholders to improve or enhance the relationship between the firm and its stakeholders (Miller et al, 2018), involvement in ESG makes the firm more sensitive to the needs of its stakeholders (Porter & Kramer, 2011). In turn, companies can gain a more comprehensive and deeper understanding of the needs of their stakeholders (e.g., consumers) and thus seek more market opportunities to develop new products or services (Murcia, 2021).…”
Section: Differentiation Strategies and Firms' Esg Involvementmentioning
confidence: 99%
“…For example, researchers have suggested that business‐level CSR activities can be in the areas of philanthropy, improving operational effectiveness and transforming the business model (Rangan et al, 2015). A recent empirical study has reported that a firm's progressive CSR positively affects the rate of new product introductions, whilst the impact of rational CSR is conditional on the firm's absorptive capacity (Murcia, 2021). Twenty‐nine studies considered business CSR activities and analysed their impacts at the product brand level.…”
Section: Review Findings and Synthesismentioning
confidence: 99%
“…29,Mizerski et al (2002),Cui et al (2003),,Dean (2003),Phau and Ong (2007),Pirsch et al (2007),Bower and Grau (2009), Chang et al (2009), Halme and Laurila (2009), Peloza and Shang (2011), Lii et al (2011), Lii and Lee (2012), Kotler et al (2012), Robinson et al (2012), Westberg and Pope (2014), Jeong et al (2013), Rangan et al (2015), Chen and Huang (2016), Austin and Gaither (2016), Hamby (2016), Kull and Heath (2016), Hilderbrand et al (2017), Howie et al (2018). Chen et al (2018), Chen and Huang (2018), Lim et al (2018), Lee and Johnson (2019), Lee et al (2021)Other 13Wartick and Cochran (1985),Fouts (1997), Weaver et al (1999),Du et al (2007),Turker (2008),Matten and Moon (2008),Liu et al (2010),Dowling and Moran (2012),Aguinis and Glavas (2013),Schons and Steinmeier (2015),Murcia (2021), Rahman and Blake (2021),Nickerson et al (2022) a Three articles have considered more than one basis for classification.…”
mentioning
confidence: 99%
“…Scholars believe that CSR benefits a company's innovation activities by enhancing their interactions with stakeholders (Luo & Du, 2015), increasing their R&D resources (Song et al, 2019), and generating a positive attitude of R&D activities among the corporate leadership (Chkir et al, 2020). The existing literature indicates that CSR increases R&D investment (Luo & Du, 2015) or reduces R&D input (Gallego‐Alvarez et al, 2011), increases patents (Wu et al, 2018), introduces new products (Murcia, 2020; Song et al, 2019), and further boosts various types of R&D outputs, such as responsible innovations (Hadj, 2020) and eco‐innovations (Pan et al, 2020). However, there is a lack of research on the relationship between CSR and R&D strategy.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…When CSR is integrated with corporate strategy, its key role of driving technological innovation cannot be ignored (Bocquet et al, 2013). Many researchers have studied the influence of CSR on R&D and innovation, such as R&D input (Gallego‐Alvarez et al, 2011), patents (Wu et al, 2018), new product introduction (Hur et al, 2014; Murcia, 2020), and new production success (Song et al, 2019). However, constrained by the input–output mindset, these scholars have largely ignored the role of CSR in the R&D decision making process.…”
Section: Introductionmentioning
confidence: 99%